A Business Model Archetype Suitable for Both Non-profit-making and Profit-making Organizations - Kavvadia, Helen (Current Topics on Business, Economics and Finance Vol. 7, 2023)
The aim of this chapter is to propose a business model archetype suitable for both non-profit-making and profit-making organizations, given that business models are equally useful in the establishment, evolution, and analysis of non-profit organizations. Many innovative approaches may contribute to delivering sustainability through business models, but have not been collated under a unifying theme of business model innovation. Sustainable business model archetypes are introduced to describe groupings of mechanisms and solutions that may contribute to building up the business model for sustainability. Consequently, the definitions and archetypes of business models proposed in the extant literature have addressed predominantly profit-making organizations. There is a genuine need for archetype models for nonprofits because such organisations are involved in both national and global economic governance. With this in mind, the paper reframes business models using a non-entrepreneurial lens and suggests a new archetype that can be applied universally to all organisations, whether they are for-profit, non-profit, public, or private. A “hybrid” archetype is developed, synthesizing existing business model archetypes while extending their reach to better embrace the overarching core logic of organizations, reflecting the political mandate of not-for-profit entities and the business remit of firms. Business models are mainly crafted and used internally by organizations as tools to establish or guide them through their establishment and evolution, as they “provide a powerful way for executives to analyze and communicate their strategic choices”. The proposed archetype's validity is examined in two international not-for-profit organisations, and it is found to be a useful conceptual framework for understanding how they make decisions and formulate policies. Furthermore, the testing process demonstrates that business models, when devised externally and retrospectively, can be equally well used in hindsight as organizational analysis tools, possibly conjointly with other methods.